2020
DOI: 10.5191/jiaee.2020.27102
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Resistance to Service-Learning’s Use in the Preparation of Teachers for Secondary Agricultural Education: A Reframing of the Method’s Diffusion Challenges

Abstract: Although service-learning (SL) has shown promise, its adoption as a method of instruction in secondary agricultural education remains tentative. As such, this philosophical investigation examined how resistance to SL might be uniquely manifested in the context of teacher preparation and the implications for agricultural education if viewed through the lens of Rogers’ (2003) diffusion of innovations theory. After synthesizing related research and theory, we argue the method of instruction’s barriers to adoption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…As such, we call for marketers of agricultural products to develop modern branding strategies for traditional food products. We also concluded that the findings of this study contributed to knowledge regarding the need to reevaluate and possibly amend food label laws and regulations to ensure greater acceptance (Roberts & Edwards, 2020). Therefore, agricultural advocates and community groups should begin to reexamine food labeling policy to determine the necessary changes that could be made to create a more transparent future.…”
Section: Conclusion Discussion Implications and Recommendationsmentioning
confidence: 72%
“…As such, we call for marketers of agricultural products to develop modern branding strategies for traditional food products. We also concluded that the findings of this study contributed to knowledge regarding the need to reevaluate and possibly amend food label laws and regulations to ensure greater acceptance (Roberts & Edwards, 2020). Therefore, agricultural advocates and community groups should begin to reexamine food labeling policy to determine the necessary changes that could be made to create a more transparent future.…”
Section: Conclusion Discussion Implications and Recommendationsmentioning
confidence: 72%
“…Although participants reported they experienced growth in their leadership style and in their career as a result of participating in LEAD, the extent of the growth varied substantially. Further, the rural Black leaders in this study were largely lack knowledge of leadership opportunities, resources, and social connections (Roberts & Edwards, 2020). For example, all participants spoke about the importance of networking and securing outside resources, i.e., revitalization programs and grants, to enhance their rural Black communities.…”
Section: Conclusion Discussion Implications and Recommendationsmentioning
confidence: 98%